When Local Models Fail. - Epstein, Brian. (Tufts University. Tisch Library., 2017)
Models treating the simple properties of social groups have a common shortcoming. Typically, they focus on the local properties of group members and the features of the world with which group members interact. I consider economic models of bureaucratic corruption, to show that (a) simple properties of groups are often constituted by the properties of the wider population, and (b) even sophisticated models are commonly inadequate to account for many simple social properties. Adequate models and social policies must treat certain factors that are not local to individual members of the group, even if those factors are not causally connected to those individuals.